Corner separation control in compressor stators with jets from the blade leading edge. (February 2023) - Zheng, Huan; Zhou, Zhenggui
Corner separation occurs easily in highly loaded compressor stators. This paper proposes a novel slot inside the stator blade, with the slot inlet located at the blade leading edge and the slot outlet located at the suction surface, by using the momentum of the incoming flow to form a high velocity jet to control the development of the boundary layer on the blade suction surface. For 3D compressor cascades, the influence of the key geometrical slot parameters on the flow fields in the slot and cascade passage and the aerodynamic performance of the cascade were investigated with a numerical method. Then, the stator blades in a highly loaded compressor stage were slotted to improve the flow in the stator blade passages. The main results can be summarized as follows. The use of slotted blades in the cascade effectively suppresses corner separation. When the cascade inlet velocity is high or the inlet flow is at a positive attack angle, the separation control effect improves. In the highly loaded compressor stage, slotted stator blades considerably reduced the flow loss at the stator corner, and the stage efficiency increased over the entire flow rate range. Furthermore, two cascades with unslotted and slotted blades were tested. The experimental and numerical results were consistent, demonstrating that the total pressure loss coefficient of a cascade can be effectively reduced by slotting the blades in the cascade.